Chemical Antioxidant Quality Markers of Chrysanthemum morifolium Using a Spectrum-Effect Approach - Lu, Yi-Fan; Li, Ding-Xiang; Zhang, Ran; Zhao, Lin-Lin; Qiu, Zhen; Du, Yan; Ji, Shuai; Tang, Dao-Quan (Frontiers in Pharmacology, 2022)
Traditionally, the quality evaluation of Chrysanthemum morifolium (CM) cv. (Juhua) attributes its habitats and processing methods, however, this strategy of neglecting bioactive ingredients usually results in deviation of quality evaluation. This study aims to explore the quality marker (Q-marker) based on spectrum-effect relationship and quality control strategy of CMs. The chromatographic fingerprint of 30 batches of CMs from five different habitats including Hang-baiju, Gongju, Huaiju, Taiju and Boju were constructed by high performance liquid chromatography and analyzed through chemometrics methods such as similarity analysis (SA), cluster analysis (CA) and principal component analysis (PCA). The common peaks were quantified by external standard method and relative correction factor method. The in-vitro radical scavenging capacity assays of DPPH•, •OH and ABTS• were carried out. The Q-marker was explored by the correlation analysis between the contents of common peaks and in-vitro radical scavenging capacity, and then used to evaluate the quality of 30 batches of CMs. A total of eight common peaks were appointed in 30 batches of CMs, and the similarities of 30 batches of CMs ranged from 0.640 to 0.956. CA results showed that 30 batches of CMs could be divided into five categories with reference to the Euclidean distance of 5. PCA results showed that the common peaks played a major role in the differential contribution of CMs. The quantification of the common peaks hinted that their contents possessed significant variation whether for different species or the same species of CMs. The correlation analysis showed that chlorogenic acid, 3,5-O-dicaffeoylquinic acid, unknown peak 1, 4,5-O-dicaffeoylquinic acid and kaempferol-3-O-rutinoside could be used as the Q-markers for the quality evaluation of 30 batches of commercially available CMs. The analysis strategy that combines chromatographic fingerprint analysis, multiple ingredients quantification, in-vitro anti-oxidant activity evaluation and spectrum-effect relationship analysis clarified the therapeutic material basis and discovered the Q-markers, which possibly offers a more comprehensive quality assessment of CMs.